Evaluation of optimized breath‐hold and free‐breathing 3D ultrashort echo time contrast agent‐free MRI of the human lung. Issue 5 (13th October 2015) - Gai, Neville D.; Malayeri, Ashkan; Agarwal, Harsh; Evers, Robert; Bluemke, David
Abstract : Purpose: To evaluate an optimized stack of radials ultrashort echo time (UTE) 3D magnetic resonance imaging (MRI) sequence for breath‐hold and free‐breathing imaging of the human lung. Materials and Methods: A 3D stack of ultrashort echo time radials trajectory was optimized for coronal and axial lower‐resolution breath‐hold and higher‐resolution free‐breathing scans using Bloch simulations. The sequence was evaluated in 10 volunteers, without the use of contrast agents. Signal‐to‐noise ratio (SNR) mean and 95% confidence interval (CI) were determined from separate signal and noise images in a semiautomated fashion. The four scanning schemes were evaluated for significant differences in image quality using Student's t ‐test. Ten clinical patients were scanned with the sequence and findings were compared with concomitant computed tomography (CT) in nine patients. Breath‐hold 3D spokes images were compared with 3D stack of radials in five volunteers. A Mann–Whitney U ‐test was performed to test significance in both cases. Results: Breath‐hold imaging of the entire lung in volunteers was performed with SNR (mean = 42.5 [CI]: 35.5–49.5; mean = 34.3 [CI]: 28.6–40) in lung parenchyma for coronal and axial scans, respectively, which can be used as a quick scout scan. Longer respiratory triggered free‐breathing scan enabled high‐resolution UTE scanning with mean SNR of 14.2 ([CI]: 12.9–15.5) and 9.2 ([CI]: 8.2–10.2) for coronal and axial scans, respectively. Axial free‐breathing scans showed significantly higher image quality ( P  = 0.008) than the three other scanning schemes. The mean score for comparison with CT was 1.67 (score 0: n  = 0; 1: n  = 3; 2: n  = 6). There was no significant difference between CT and MRI ( P  = 0.25). 3D stack of radials images were significantly better than 3D spokes images ( P < 0.001). Conclusion: The optimized 3D stack of radials trajectory was shown to provide high‐quality MR images of the lung parenchyma without the use of MRI contrast agents. The sequence may offer the possibility of breath‐hold imaging and provides greater flexibility in trading off slice thickness and parallel imaging for scan time. J. Magn. Reson. Imaging 2016;43:1230–1238.